Job Placement Rates Among First-Generation Hospitality Students. Issue 4 (2nd October 2019) - Shroder, Laura M.
ABSTRACT: This study compared the job placement status of 1st-generation college students and traditional students graduating from a 4-year hospitality program. Data were collected through a survey of graduating seniors. A chi-square analysis revealed that 1st-generation college students were 3 times less likely to have a job in place at graduation. This finding is significant for university programs to examine their resources and programming to ensure that 1st-generation students' needs are addressed.